Effects of eight different ligament property datasets on biomechanics of a lumbar L4-L5 finite element model. (21st March 2018) - Naserkhaki, S.; Arjmand, N.; Shirazi-Adl, A.; Farahmand, F.; El-Rich, M.
Abstract: Ligaments assist trunk muscles in balancing external moments and providing spinal stability. In absence of the personalized material properties for ligaments, finite element (FE) models use dispersed data from the literature. This study aims to investigate the relative effects of eight different ligament property datasets on FE model responses. Eight L4-L5 models distinct only in ligament properties were constructed and loaded under moment (15 N m) alone or combined with a compressive follower load (FL). Range of motions (RoM) of the disc-alone model matched well in vitro data. Ligament properties significantly affected only sagittal RoMs (∼3.0–7.1° in flexion and ∼3.8–5.8° in extension at 10 N m). Sequential removal of ligaments shifted sagittal RoMs in and out of the corresponding in vitro ranges. When moment was combined with FL, center of rotation matched in vivo data for all models (3.8 ± 0.9 mm and 4.3 ± 1.8 mm posterior to the disc center in flexion and extension, respectively). Under 15 N m sagittal moments, ligament strains were often smaller or within the in vitro range in flexion whereas some posterior ligament forces approached their failure forces in some models. Ligament forces varied substantially within the models and affected the moment-sharing and internal forces on the disc and facet joints. Intradiscal pressure (IDP) had the greatest variation between models in extension. None of the datasets yielded results in agreement with all reported measurements. Results emphasized the important role of ligaments especially under larger moments and the need for their accurate representation in search for valid spinal models.